Layout timing of mining roadways considering goaf and roof stability - Yuan, Fang; Tang, Jianxin; Kong, Lingrui; Li, Cheng (Frontiers in Earth Science, 2023)
Reasonable roadway layout timing can effectively reduce the deformation of the rock surrounding the roadway and relieve mining and excavation tension. To analyze the mine pressure behavior of the gob-side entry at the edge of a goaf and the roof stability along the strike direction in the middle of a goaf, field observations and particle flow discrete element numerical simulation (PFC) method were performed. The results showed that deformation of the surrounding rock mainly occurred because of roof-to-floor convergence, caused mainly by floor heave. The mechanical behaviors of the rock mass, such as elasticity, fracture, and post-peak softening, could be simulated using the model of a jointed rock mass generated by rigid block elements in the PFC method. Considering the length of the violent and reduced roof activity zones and the activity duration as the indices to determine the basic stability of the goaf, the basic stability distance of the tested goaf edge was 135 m after coal seam mining, and the basic stability time was 27 days. The basic stable distance in the middle of the goaf was 183.4 m after coal seam mining, and the basic stability time was 37 days.